2010
DOI: 10.1504/ijmms.2010.036067
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the milling of titanium aluminide alloys

Abstract: The work here presented is framed in the line of development manufacturing processes for a new generation of slight materials with good mechanical properties, the Gamma TiAl alloys. These alloys were developed to achieve a reduction of weight in different components for aviation and automotion where very high temperatures are the main factor. In this application fields, several components must withstand high temperatures maintaining a high resistance. The superalloys of type Gamma TiAl are an attractive altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…These trends resulted also in agreement with the results reported by Branoagirre for other gamma-TiAl alloys, manufactured as solidified ingot and extruded after solidification [11,12]. In dry milling, the experimental data for tool life estimation are well fitted by the following full quadratic model (correlation index R=0.99), whose behavior is shown in Fig.…”
Section: Tool Wearsupporting
confidence: 90%
“…These trends resulted also in agreement with the results reported by Branoagirre for other gamma-TiAl alloys, manufactured as solidified ingot and extruded after solidification [11,12]. In dry milling, the experimental data for tool life estimation are well fitted by the following full quadratic model (correlation index R=0.99), whose behavior is shown in Fig.…”
Section: Tool Wearsupporting
confidence: 90%
“…In addition, tool flank wear and cutting speed were found to have the greatest effect on residual stress. Beranoagirre and López de Lacalle (2010) presented the results of milling tests on three different types of gamma TiAl alloys: the MoCuSi type in ingot and extruded form, and the TNB type in ingot form. They analyzed the flank wear as a function of cutting time for different cutting conditions, and found that the cutting speed has the main effect on the tool life of hard metal end milling tools.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in machinability of gamma titanium aluminides is still increasing, focussing on milling [14,15], drilling [16] and turning [17][18][19] processes. However, further work is needed to optimize machining strategies leading to high productivity at aerospace quality levels, where surface integrity is indispensable for the in-use component, focusing on tool and process design as well as the development of adapted high performance lubricoolant strategies.…”
Section: Introductionmentioning
confidence: 99%